Implementasi Pendekatan Pembelajaran â€œAbout, In, & For The Environmentâ€ dengan Model Problem-Based Learning dalam Meningkatkan Literasi Lingkungan Siswa SMA - Putri, Sevia Tasya; Nuryadin, Atin; Efwinda, Shelly (Universitas PGRI Semarang, 2024)
Abstract. This study aims to determine the level of environmental literacy of students and the results of applying the